Woven endobridge device compared to stent-assisted coiling and microsurgical clipping for intracranial aneurysms - Adil Ahmed; Ocílio Ribeiro Gonçalves; Paweł Łajczak; Kenzo Ogasawara Donato; Maria Antonia Oliveira Machado Pereira; Filipe Virgilio Ribeiro; Anderson Matheus Pereira da Silva; Jose Fernando Olvera-Castro; João Vitor Andrade Fernandes; Muhammad Nawaz Khan; Syed Sarmad Bukhari (Medicine, 2026)
Background: Endovascular techniques and devices, including Woven EndoBridge (WEB) and stent-assisted coiling (SAC), expand the choice of therapies for complex aneurysms, while the evidence directly comparing them to microsurgical clipping (MSC) remains very limited. This meta-analysis compares the safety and efficacy of WEB vs SAC and MSC in patients with ruptured and unruptured intracranial aneurysms. Methods: This study followed PRISMA guidelines. A comprehensive search of PubMed, Embase, and Scopus identified comparative cohort studies of WEB vs SAC and MSC for wide-neck intracranial aneurysms. Outcomes included occlusion, favorable functional/neurological outcome, defined as a modified Rankin Scale (mRS) score of 0–2, complications, and mortality. Statistical analyses were performed in R Studio. Heterogeneity was assessed with I 2 and leave-one-out (LOO) sensitivity, and publication bias with funnel plots and Egger’s test. Results: Seventeen observational studies with a total of 2289 patients were included. When compared with mechanical circulatory support (MSC), the WEB device was associated with lower rates of adequate occlusion (RR 0.77; 95% CI 0.69–0.86; P < .001) and higher rates of incomplete occlusion (RR 4.61; 95% CI 2.12–10.01; P < .001). No significant differences were found in mortality or favorable neurological outcomes (defined as modified Rankin Scale [mRS] 0–2). In comparisons with stent-assisted coiling (SAC), the WEB device showed similar rates of complete occlusion (RR 0.98; P = .617), retreatment (RR 0.79; P = .508), and thromboembolic complications (RR 0.59; P = .137). The WEB device did demonstrate a significantly lower incidence of procedure-related complications (RR 0.49; 95% CI 0.29–0.85; P = .011). Conclusion: MSC offers the most durable occlusion, whereas WEB and SAC are less invasive, with WEB showing better safety than SAC but lower durability than MSC, supporting individualized, evidence-based treatment.